Habilitering for voksne i spesialisthelsetjenesten: Utvikling og utprøving av brukerundersøkelse - Erik Søndenaa; Stein Ketil Sauarlia; Britt Hukkelås; Sidsel Jullumstrø (Septentrio Academic Publishing, 2016)
Habilitation specialist health-services: measure of processes of care for adults Habilitation specialist service for adults in Sør-Trøndelag has developed and implemented a model for user perceptions over the last five years. As users of the service consist of diverted parts, the work has aimed at obtaining complement responses from the different parts in their experience of this specialist services. The purpose of this article has been to present the development of a user survey and some findings after testing. Key information was collected for 328 active patient cases over a limited period. From these cases views from patients, relatives and municipal care have been collected. Besides obtaining feedback from users, the survey provides a basis for compiling user groups and studying different types of users based on key information.